Contested multilateralism 2.0 and regional order transition: causes and implications - He, Kai (Pacific review, 2019)
This article proposes a new concept of 'contested multilateralism 2.0' to describe the puzzling institutional building efforts by non-ASEAN members after the 2008 global financial crisis (GFC) in the Asia-Pacific. It suggests that different to 'multilateralism 1.0' of the 1990s, which was mainly led by ASEAN, this wave of multilateralism has been initiated by other powers, such as the United States, China, Japan, Australia and South Korea, either by forming new institutions or by reinvigorating existing ones. This article advances an institutional balancing argument. It suggests that 'contested multilateralism 2.0' is a result of institutional balancing among major states under the conditions of high strategic uncertainty and high economic interdependence after the GFC. One unintended consequence may be that it could well lead to a more peaceful transformation of the regional order in the Asia-Pacific if regional security hotspots, such as the Korean crisis and the South China Sea dispute, can be managed appropriately.